Slide system

JP2025034728APending Publication Date: 2025-03-13MITSUBISHI HEAVY IND LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023141300
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0012】 本開示に係る摺動システムによれば、窒素およびタンタルを含有させたアモルファス炭素膜で摺動面を覆った摺動部材をモリブデンジチオカーバメート含有潤滑剤の潤滑下で使用することで従来よりも摩擦低減効果を高められる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034728000001_ABST
    Figure 2025034728000001_ABST
Patent Text Reader

Abstract

To provide a slide system having larger friction reduction effect than conventional arts.SOLUTION: A slide system according to the present disclosure includes a pair of slide members having opposing slide faces capable of relative displacement, and a lubricant disposed between slide interfaces of the slide members, wherein at least one of the slide faces is coated with an amorphous carbon film containing nitrogen and tantalum, and the lubricant includes a base oil and molybdenum dithiocarbamate. Molybdenum dithiocarbamate is preferably included in the lubricant at a molybdenum conversion of 1400 ppm or over.SELECTED DRAWING: Figure 14
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a sliding system using a carbon film and a lubricant formulation. [Background technology]

[0002] In sliding parts such as piston rings in engines, boundary lubrication occurs during repeated reciprocating motion, which increases wear or increases the friction coefficient, resulting in a decrease in efficiency. For this reason, there is a demand for low wear and low friction in sliding parts in the boundary lubrication region.

[0003] As a measure against wear, a diamond-like carbon (DLC) film is sometimes formed on the sliding surface of a sliding member (see Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-17174 A [Patent Document 2] JP 2013-136664 A [Patent Document 3] Special Publication No. 2019-513856 Summary of the Invention [Problem to be solved by the invention]

[0005] Although DLC films exhibit good wear resistance in engine oil, their friction reduction effect is not significant.

[0006] In Patent Documents 1 and 2, the DLC film is doped with a metal element to improve the friction reducing effect in engine oil.

[0007] In Patent Document 3, a lubricant compound is mixed into the engine oil to improve the friction reducing effect.

[0008] However, the techniques described in Patent Documents 1 to 3 still have a small effect on reducing friction, and there is room for improvement.

[0009] The present disclosure has been made in consideration of the above circumstances, and has an object to provide a sliding system that has a greater effect of reducing friction than conventional systems. [Means for solving the problem]

[0010] In order to solve the above problems, the sliding system of the present disclosure employs the following measures.

[0011] The present disclosure provides a sliding system comprising a pair of sliding members having opposing sliding surfaces capable of relative movement, and a lubricant interposed between the sliding surfaces of the sliding members, wherein at least one of the sliding surfaces is coated with an amorphous carbon film containing nitrogen and tantalum, and the lubricant contains a base oil and molybdenum dithiocarbamate. Effect of the Invention

[0012] According to the sliding system of the present disclosure, a sliding member having a sliding surface covered with an amorphous carbon film containing nitrogen and tantalum is used under lubrication with a lubricant containing molybdenum dithiocarbamate, thereby making it possible to enhance the friction reduction effect compared to conventional methods. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a diagram showing an example of a system configuration for forming an amorphous carbon film according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of the sliding part of a roller-on-disk friction tester. [Diagram 3] FIG. 1 is a diagram showing the relationship between the addition of elements to DLC and the addition of MoDTC to a lubricant and the friction coefficient. [Figure 4] FIG. 1 is a graph showing the friction progression curve in Test No. 1-1 (without MoDTC addition, SUJ2). [Diagram 5] FIG. 1 is a graph showing friction progression curves in Test No. 1-2 (without MoDTC addition, ta-C). [Figure 6] FIG. 1 is a graph showing friction progression curves in Test No. 1-3 (without MoDTC addition, ta-C:Ta). [Figure 7] FIG. 1 is a graph showing friction progression curves in Test No. 1-4 (no MoDTC added, ta-CNx). [Figure 8] FIG. 1 is a graph showing friction progression curves in Test No. 1-5 (no MoDTC added, ta-CNx:Ta). [Figure 9] FIG. 1 is a graph showing a friction progress curve in Test No. 2-1 (MoDTC 3000 ppm added, SUJ2). [Figure 10] FIG. 1 is a graph showing a friction progress curve in Test No. 2-2 (MoDTC 3000 ppm added, ta-C). [Figure 11] FIG. 1 is a graph showing a friction progress curve in Test No. 2-3 (MoDTC 3000 ppm added, ta-C:Ta). [Figure 12] FIG. 1 is a graph showing friction progress curves in Test No. 2-4 (MoDTC 3000 ppm added, ta-CNx). [Figure 13] FIG. 1 is a graph showing friction progress curves in Test No. 2-5 (MoDTC 3000 ppm added, ta-CNx:Ta). [Figure 14] FIG. 1 is a graph showing the relationship between the amount of MoDTC added and the friction coefficient under PAO8 lubrication. [Figure 15] FIG. 1 is a graph showing friction progression curves in Test No. 3-1 (no MoDTC added, ta-CNx:Ta). [Figure 16] FIG. 1 is a graph showing a friction progress curve in Test No. 3-2 (MoDTC 700 ppm added, ta-CNx:Ta). [Figure 17] FIG. 1 is a graph showing a friction progress curve in Test No. 3-3 (MoDTC 1400 ppm added, ta-CNx:Ta). [Figure 18] FIG. 1 is a graph showing friction progress curves in Test No. 3-4 (MoDTC 3000 ppm added, ta-CNx:Ta). [Figure 19] FIG. 1 is a graph showing the relationship between the amount of MoDTC added and the friction coefficient under diesel oil lubrication. [Figure 20] FIG. 1 is a diagram illustrating an EDS analysis range. [Figure 21] This is an image (SUJ2) showing the results of EDS analysis. [Figure 22] 1 is an image (ta-C) showing the results of EDS analysis. [Figure 23] 1 is an image (ta-CNx) showing the results of EDS analysis. [Figure 24] 1 is an image showing the results of EDS analysis (ta-C:Ta). [Diagram 25] 1 is an image showing the results of EDS analysis (ta-CNx:Ta). [Figure 26] FIG. 2 is a graph showing the relationship between tantalum content and coefficient of friction. [Figure 27] FIG. 1 shows a friction progression curve for a tantalum content of 6%. [Figure 28] FIG. 1 shows a friction progression curve for a tantalum content of 8%. [Figure 29] FIG. 1 shows a friction progression curve for a tantalum content of 9%. [Diagram 30] FIG. 1 shows friction progress curves in tests using two types of disks with different surface roughness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of a sliding system according to the present disclosure will be described with reference to the drawings. (Sliding System) The sliding system according to this embodiment includes a pair of sliding members having opposing sliding surfaces capable of relative movement, and a lubricant interposed between the sliding surfaces of the sliding members.

[0015] The sliding system can be applied to sliding parts in engines or other environments where lubricants based on synthetic oils (PAO (poly-alpha-olefin), esters) or mineral oils are used.

[0016] In a pair of sliding members, the sliding surface of at least one of the sliding members is coated with an amorphous carbon film. For example, when the sliding members are a piston ring and a cylinder of an engine, the amorphous carbon film can be provided on the sliding surface of the piston ring.

[0017] The amorphous carbon film is a non-crystalline hard film, and is also called diamond-like carbon (DLC). The amorphous carbon film in this embodiment contains carbon, nitrogen, and tantalum.

[0018] The tantalum content in the amorphous carbon film is not less than 5 atomic % and not more than 9 atomic %.

[0019] The lubricant is disposed between the sliding surfaces of a pair of sliding members to lubricate the relative movement of the sliding members. The lubricant contains a base oil and molybdenum dithiocarbamate (MoDTC).

[0020] The content of the base oil in the lubricant is 80% by weight or more and 95% by weight or less, preferably 85% by weight or more and 95% by weight or less. The base oil is engine oil, synthetic oil (PAO (poly-alpha-olefin), ester) or mineral oil.

[0021] The content of MoDTC in the lubricant is preferably 1400 ppm or more in terms of molybdenum (Mo).

[0022] The lubricant may contain additives such as friction modifiers, including fatty acid esters, higher alcohols and their compounds, molybdenum disulfide, aliphatic amines, amide esters and amine-based compounds, polymethacrylates (PMA), polyisobutylene olefin copolymers (OCP), ethylene-styrene copolymers (EPC), and the like.

[0023] In a pair of sliding members, by forming an amorphous carbon film containing nitrogen and tantalum (ta-CNx:Ta) on at least one of the sliding surfaces and by interposing a lubricant containing MoDTC between the sliding surfaces, it is possible to reduce the friction coefficient in the sliding part compared to conventional methods.

[0024] (Method of forming amorphous carbon film) A hybrid plasma DLC coating system can be used to form the amorphous carbon film. An example of the configuration of the hybrid plasma DLC coating system is shown in Figure 1.

[0025] The hybrid plasma DLC coating system 10 is a deposition apparatus that combines a Filtered Cathodic Vacuum Arc (FCVA) apparatus 20, an Anode Linear Ion Source (ALIS) 30, and an Unbalanced Magnetron Sputter (UBMS) apparatus 40.

[0026] The FCVA device 20 supplies carbon to the surface of the substrate 1 by a filtered cathodic vacuum arc method (a type of PVD). The ALIS 30 supplies nitrogen to the surface of the substrate 1 by an anode liner ion source method (a type of plasma CVD). The UBMS device 40 supplies tantalum to the surface of the substrate 1 by an unbalanced magnetron sputtering method (a type of PVD).

[0027] The substrate 1 can be placed on a rotatable substrate holder 3 in a vacuum chamber 2. By moving the substrate 1 by rotating the substrate holder 3, carbon, nitrogen, and tantalum can be alternately supplied to the surface of the substrate 1. It should be noted that the present invention is not limited to FIG. 1, and carbon, nitrogen, and tantalum may be supplied simultaneously from the same direction.

[0028] The process for forming the amorphous carbon film includes (S1) to (S5) in this order. (S1) A clean substrate 1 is placed on a substrate holder 3. (S2) The inside of the vacuum chamber 2 is, for example, 4.5×10 -4 The vacuum is drawn until the pressure drops to below 1 Pa. (S3) The surface of the carbon target is cleaned by generating an arc discharge on the carbon target (Graphite cathode) using the FCVA device 20.

[0029] (S4) Argon gas is introduced into the vacuum chamber 2 from the gas supply unit 31 of the ALIS 30. At this time, an argon ion beam generated from the argon gas is irradiated toward the substrate 1 while the substrate holder 3 is rotated. This removes impurities and the like from the surface of the substrate 1, cleaning it. At this time, no argon remains on the substrate 1.

[0030] (S5) While the substrate holder 3 is being rotated, an amorphous carbon film containing nitrogen and tantalum (ta-CNx:Ta) is formed on the substrate 1 by the FCVA apparatus 20, the ALIS 30, and the UBMS apparatus 40.

[0031] The nitrogen content in the amorphous carbon film can be adjusted by the flow rate of nitrogen gas supplied into the vacuum chamber 2 . The tantalum content in the amorphous carbon film can be adjusted by the bias of the UBMS device.

[0032] The following describes the effects obtained by combining a sliding member whose surface is covered with an amorphous carbon film containing nitrogen and tantalum with a lubricant containing MoDTC.

[0033] (Reciprocating friction test) 1. Test Method A roller-on-disk friction tester was used for the test. Figure 2 shows a schematic diagram of the sliding part of the roller-on-disk friction tester. The parts corresponding to the pair of sliding members described in the above embodiment are a roller 50 and a disk 51. The roller 50 was made of SUJ2 material (surface roughness Ra ≒ 0.05 μm). The disk 51 was made of Ni-Cr steel (surface roughness Ra ≒ 0.005 μm).

[0034] The amorphous carbon film 52 was formed on the surface of the roller 50. The types of the amorphous carbon film 52 formed on the surface of the roller 50 were as follows. "ta-C:" Tetrahedral amorphous carbon "ta-C:Ta" Tantalum-containing tetrahedral amorphous carbon "ta-CNx" Nitrogen-containing amorphous carbon film "ta-CNx:Ta" Tantalum and nitrogen-containing amorphous carbon film

[0035] Table 1 shows the coating specifications of each amorphous carbon film 52. [Table 1]

[0036] The disk 51 was immersed in the lubricant 53, and the lubricant 53 was placed between the roller 50 and the disk 51. The base oil of the lubricant 53 was PAO8 (polyalphaolefin 8) or diesel oil. MoDTC (ADEKA Sakuralube 525 manufactured by ADEKA Corporation) of 0 ppm to 3000 ppm in terms of Mo was added to the lubricant 53. The PAO8 used had a viscosity of 0.00792 Pa / s at 80°C.

[0037] A vertical load was applied to the roller 50 and pressed against the disk 51, and the disk 51 was moved back and forth in a straight line in the left-right direction of the paper to obtain data on the friction force. The average sliding speed was 6.3 mm / S (sliding width 6 mm). The test time was 35 minutes, and the vertical load was increased from 1 N to 2.5 N and decreased from 2.5 N to 1 N by 0.5 N every 100 cycles during the test time. The load and friction force were measured using a strain gauge installed on a leaf spring (not shown), and the sampling frequency was 100 Hz. The lubricant temperature was 80°C, and the reciprocating period was 0.33 Hz. In addition, the initial value Λ, which indicates the lubrication state, was all 0.05 or less, and the test was performed under boundary lubrication conditions. The friction coefficient was calculated by dividing the absolute value of the friction force data by the load, and the friction progress curve was obtained using the average value of the friction coefficient for five cycles.

[0038] 2. Effects of element addition to amorphous carbon film and MoDTC addition to lubricant on friction coefficient Table 2 and Figures 3 to 8 show the results of reciprocating friction tests performed on rollers coated with amorphous carbon films containing different additive elements under PAO lubrication or MoDTC-containing PAO8 lubrication. Figure 3 shows the relationship between the addition of elements to the amorphous carbon film (DLC) and the addition of MoDTC to the lubricant and the friction coefficient. Figure 4 shows the friction progress curve of Test No. 1-1. Figure 5 shows the friction progress curve of Test No. 1-2. Figure 6 shows the friction progress curve of Test No. 1-3. Figure 7 shows the friction progress curve of Test No. 1-4. Figure 8 shows the friction progress curve of Test No. 1-5. Figure 9 shows the friction progress curve of Test No. 2-1. Figure 10 shows the friction progress curve of Test No. 2-2. Figure 11 shows the friction progress curve of Test No. 2-3. Figure 12 shows the friction progress curve of Test No. 2-4. Figure 13 shows the friction progress curve of Test No. 2-5.

[0039] [Table 2]

[0040] Under PAO8 lubrication, the friction coefficient of the rollers coated with the amorphous carbon film was lower than that of the uncoated rollers. This confirmed that the friction reduction effect can be obtained by coating with the amorphous carbon film, regardless of the type or presence of added elements.

[0041] When lubricated with MoDTC-containing PAO8, the friction coefficient decreased for all materials except for ta-CNx, which was added with only nitrogen. When MoDTC was added, the friction coefficients of SUJ2, ta-C, ta-C:Ta, and ta-CNx:Ta decreased by 46%, 24%, 29%, and 62%, respectively, compared to when MoDTC was not added.

[0042] The ta-CNx:Ta coating had a higher friction coefficient than the other coatings when lubricated with PAO8 without MoDTC, but when used in combination with a lubricant containing MoDTC, the friction reduction effect was improved and the coating showed the lowest friction coefficient.

[0043] These results demonstrate that the amorphous carbon film containing nitrogen and tantalum (ta-CNx:Ta coating) exhibits the highest friction reduction effect under high-temperature reciprocating sliding conditions with MoDTC-containing PAO8 lubrication.

[0044] 3. Amount of MoDTC added (using PAO8) The change in friction coefficient when the amount of MoDTC added to the lubricant (PAO8) was changed is shown in Table 3 and Figures 14 to 18. For the roller coating, ta-CNx:Ta was used. Figure 14 is a graph showing the change in friction coefficient according to the amount of MoDTC added. Figure 15 is the friction progress curve of Test No. 3-1. Figure 16 is the friction progress curve of Test No. 3-2. Figure 17 is the friction progress curve of Test No. 3-3. Figure 18 is the friction progress curve of Test No. 3-4.

[0045] [Table 3]

[0046] According to Table 3 and Figures 14 to 18, when MoDTC was added at 700 ppm, no friction reduction effect was observed compared to when MoDTC was not added. When MoDTC was added at 1400 ppm and 3000 ppm, a decrease in the friction coefficient was confirmed. From these results, it became clear that the MoDTC content concentration in the lubricant is preferably 1400 ppm or more.

[0047] 4. MoDTC Addition Amount (Diesel Oil Used) The results of the reciprocating friction test using diesel oil as the lubricant base oil are shown in Table 4 and Figure 19.

[0048] [Table 4]

[0049] According to Table 4 and Figure 19, even when lubricated with diesel oil, the friction coefficient of the roller coated with ta-CNx:Ta was reduced by 31% by adding MoDTC (3000 ppm) compared to when no MoDTC was added. On the other hand, when MoDTC was added at 700 ppm, no reduction in the friction coefficient was observed compared to when no MoDTC was added. These results suggest that the effect of the amount of MoDTC added on the friction coefficient shows the same tendency regardless of the type of base oil.

[0050] 5. Roller surface analysis The roller test piece (dashed frame in Fig. 20) after the reciprocating friction test under the MoDTC-containing PAO8 lubrication was analyzed by energy dispersive X-ray spectroscopy (EDS). The analysis results are shown in Figs. 21 to 25. In Figs. 21 to 25, (a) is an SEM image, (b) is an Mo element mapping image, and (c) is an S element mapping image. Fig. 21 is an image of the roller test piece of SUJ2 (no coating), Fig. 22 is a ta-C coating, Fig. 23 is a ta-CNx coating, Fig. 24 is a ta-C:Ta coating, and Fig. 25 is a ta-CNx:Ta coating. In Figs. 21 to 25, the part between the two dashed lines is the part that was in contact with the disk (sliding contact surface), and the double arrows indicate the sliding direction.

[0051] The presence of S and Mo was observed in all roller specimens. 21 to 25, more S and Mo were observed on both sides of the sliding contact surface than on the sliding contact surface. This is because the S and M on the sliding contact surface were scraped off by the relative movement of the disk 51 and the roller 50, and moved to both sides. Although it is difficult to confirm in the figures, the presence of S and Mo was confirmed on the sliding contact surface as well.

[0052] S and Mo are elements derived from MoDTC. This suggests that reaction products derived from MoDTC exist on the surface of the roller test piece, and that a tribofilm consisting of these reaction products is formed in the wear track.

[0053] According to Figures 21 to 25, the presence of the most S and Mo was confirmed in the roller test piece with the ta-CNx:Ta coating (Figure 25). This result suggests that the reaction products derived from MoDTC were generated in the largest amount in the ta-CNx:Ta coating. It is considered that the tribofilm derived from MoDTC was formed more firmly in the roller test piece with the ta-CNx:Ta coating than in the other roller test pieces, which reduced the contact between the substrates and resulted in a high friction reduction effect.

[0054] On the other hand, the other coatings produced less reaction products derived from MoDTC, which may have led to more contact between the substrates and reduced friction reduction effects.

[0055] 6. Tantalum Content Three types of rollers were prepared, each coated with ta-CNx:Ta with different tantalum contents. For each roller, reciprocating friction tests were carried out under the same lubrication as above with PAO8 containing MoDTC. The MoDTC content was 3000 ppm.

[0056] The composition of the ta-CNx:Ta coated on each roller is shown in Table 5. The tantalum content in the ta-CNx:Ta was measured by Auger electron spectroscopy (AES). [Table 5]

[0057] The relationship between the tantalum content and the friction coefficient is shown in Fig. 26. Figs. 27 to 29 show friction progress curves of tests using three types of rollers with different tantalum contents. Fig. 27 shows the friction progress curve when the tantalum content is 5.61 atomic %. Fig. 28 shows the friction progress curve when the tantalum content is 7.92 atomic %. Fig. 29 shows the friction progress curve when the tantalum addition amount is 8.94 atomic %. In Figs. 27 to 29, the tantalum content is rounded up to the nearest whole number. According to Figs. 26 to 29, when the nitrogen content was around 15 atomic % and the tantalum content was in the range of 5.61 to 8.94 atomic %, no significant difference was observed in the friction reduction effect.

[0058] (Surface roughness) Two types of Ni-Cr steel disks with different surface roughness (Ra 0.01μm and 0.1μm) were prepared. Reciprocating friction tests were carried out using each disk and a roller coated with ta-CNx:Ta under the lubrication of MoDTC-containing PAO8.

[0059] The friction progress curves of the test using two types of disks with different surface roughness are shown in Figure 30. According to Figure 30, it was confirmed that if the surface roughness Ra of the part (disk) not coated with ta-CNx:Ta is in the range of 0.01 μm and 0.1 μm, the effect on the friction with the member (roller) coated with ta-CNx:Ta under the lubrication of MoDTC-containing PAO8 is low.

[0060] <Additional Notes> The sliding system described in the above-described embodiment can be understood, for example, as follows.

[0061] A sliding system according to a first aspect of the present disclosure includes a pair of sliding members having opposing sliding surfaces capable of relative movement, and a lubricant interposed between the sliding surfaces of the sliding members, wherein at least one of the sliding surfaces is coated with an amorphous carbon film containing nitrogen and tantalum, and the lubricant contains a base oil and molybdenum dithiocarbamate.

[0062] According to the above disclosure, by using a sliding member whose sliding surface is covered with an amorphous carbon film containing nitrogen and tantalum under lubrication with a lubricant containing molybdenum dithiocarbamate, the friction reducing effect can be enhanced more than ever before.

[0063] In the sliding system according to a second aspect of the present disclosure, in the first aspect, the molybdenum dithiocarbamate may be contained in the lubricant in an amount of 1400 ppm or more in terms of molybdenum.

[0064] By including molybdenum dithiocarbamate in the above range, the friction reducing effect can be more reliably enhanced in combination with an amorphous carbon film containing nitrogen and tantalum. [Explanation of symbols]

[0065] 1 Base material 2. Vacuum chamber 3 Substrate holder 10 Hybrid Plasma DLC Coating System 20 Vacuum Arc (FCVA) Equipment 30 ALIS 40 UBMS equipment 50 Lola 51 Disc 52 Amorphous carbon film (DLC) 53 Lubricants

Claims

1. A pair of sliding members having opposing sliding surfaces that can move relative to each other; A lubricant interposed between the sliding surfaces of the sliding members; Equipped with At least one of the sliding surfaces is coated with an amorphous carbon film containing nitrogen and tantalum; A sliding system, wherein the lubricant comprises a base oil and a molybdenum dithiocarbamate.

2. 2. The sliding system according to claim 1, wherein the molybdenum dithiocarbamate is contained in the lubricant in an amount of 1400 ppm or more in terms of molybdenum.

Citation Information

Patent Citations

  • Low friction sliding member

    JP2013136664A

  • Sliding machine

    JP2016017174A

  • Lubrication systems containing DLC ​​surfaces

    JP2019513856A